2020
DOI: 10.1142/s0217984920400424
|View full text |Cite
|
Sign up to set email alerts
|

Removal characteristics of shop-primer paint by laser energy density in Q-switching fiber laser cleaning

Abstract: In this study, we performed laser cleaning using a Q-switching fiber laser to remove the shop-primer paint and the oxide layer. An analysis of the surface cleaned by laser was carried out at various energy densities. The results showed that the oxide layer on the steel surface was not removed at a relatively low energy density, whereas the base metal was damaged under excessive energy density. We confirmed that it was essential to select an appropriate energy density for efficiently removing only the paint and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…According to above results, it can be concluded that the safe power intensity for the cleaning of ductile iron substrate is about 320 W, corresponding to 10.86 J/cm 2 (1.086 × 10 8 W/cm 2 ), which is close to the calculated result. According to literatures [10,[23][24][25], the thick surface layer can be completely removed by increasing cleaning times. us, in following experiments, average laser power is adjusted to 320 W and other parameters are kept the same with prior experiments.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…According to above results, it can be concluded that the safe power intensity for the cleaning of ductile iron substrate is about 320 W, corresponding to 10.86 J/cm 2 (1.086 × 10 8 W/cm 2 ), which is close to the calculated result. According to literatures [10,[23][24][25], the thick surface layer can be completely removed by increasing cleaning times. us, in following experiments, average laser power is adjusted to 320 W and other parameters are kept the same with prior experiments.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Zapka W. et al [14] conducted the laser-induced removal of particles from surfaces with different laser wavelengths. Harris C. D. et al and Kim J. E. [15,16] studied and verified the removal mechanism of laser cleaning via laser cleaning experiments conducted on metallic surface oxide. Lu Y. F. et al [17,18] characterized the ejected particles during laser cleaning using the recently developed "steam laser cleaning" method.…”
Section: Introductionmentioning
confidence: 99%
“…Because it is painted thicker than 200 µm on ships, its removal presents a significant challenge when using both laser cleaning and mechanical cleaning technologies. Before proceeding with this study, our researchers conducted a previous study to remove 200 µm of epoxy paint from the steel surface of ships using a fiber laser cleaning system with an average power of 100 W without a beam scanning pattern function [13][14][15][16][17]. As a result, it was possible to remove the paint from the metal surface, but there remained several problems to be solved in order to expand the cleaning area and obtain effective results.…”
Section: Introductionmentioning
confidence: 99%